The FAN program plan: Creating a healthy church environment for physical activity and healthy eating - John A. Bernhart; Caroline G. Dunn; Sara Wilcox; Jessica Stucker; Deborah Kinnard (Elsevier, 2022)
Background: Faith, Activity, & Nutrition (FAN) helps churches create a healthier environment for physical activity (PA) and healthy eating (HE) through policy, systems, and environmental changes. Objective: The purpose of this paper is to describe the implementation, evaluation, and revision of the FAN Program Plan across a two-phase study to help churches create guidelines and policies for PA and HE. Methods: In Phase 1, church committees attended trainings led by Community Health Advisors (CHA) where they assessed current practices to PA and HE. Committees used the FAN Program Plan to outline an implementation plan to increase opportunities, programs, messages, pastor support, and guidelines/practices for PA and HE. FAN Program Plans were submitted to the research team for review. Findings from Phase 1 plans directed revisions in program materials for Phase 2, where the submission and review processes were repeated. Results: Review of Phase 1 FAN Program Plans (53/54 churches submitted a Program Plan) revealed that church committees confused guidelines/practices with programs and had trouble differentiating programs for PA and HE from providing opportunities (i.e., building PA/HE into existing events). The CHA training, FAN church committee training, FAN Program Plan, and other documents were revised to use the term "guidelines (policies)" instead of "guidelines/practices." In addition, CHAs facilitated a training section on guidelines (policies) to committees, and a guidelines (policies) section was added in the FAN Program Plan and other program documents. These changes in Phase 2 were helpful for differentiating policies from programs and programs from opportunities in FAN Program Plans (53/115 churches submitted a Program Plan), although some confusion remained. Conclusions: This study underscored challenges churches may have in setting policies for PA and HE and discusses strategies to address these challenges in future faith-based initiatives.